Use of whey protein concentrate, dried buttermilk, and porcine plasma protein to replace dried skim milk in diets for weanling pigs - Richert, B.T.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred thirty-two weanling pigs, with an average age of 19 d and average weight of 8.4Ib, were used in a 28-d growth assay to determine the effects of replacing dried skim milk (DSM) with dried whey protein concentrate (WPC), dried buttermilk (DBM), and spray-dried porcine plasma (SDPP). Treatments were 1) 20% DSM20% dried whey-based control, 2) WPC used to replace the DSM of Diet 1, 3) DBM used to replace the DSM of Diet 1, and 4) SDPP and lactose used to replace the DSM of Diet 1. All diets were formulated to 1.4% lysine, 25% lactose, 5% fat, .9% Ca, and .8% P. These diets were fed from d 0 to 14 with a corn-soybean meal - dried whey - fish meal - based diet fed to all pigs from d 14 to 28. For d 0 to 14, pigs fed the alternative protein sources (WPC, DBM, and SDPP) had average daily gain (ADG), average daily feed intake (ADFI), and feed/gain (FIG) similar to pigs fed DSM. Pigs fed SDPP had the greatest ADG and ADFI but poorer FIG than pigs fed WPC and DBM. Pigs fed WPC had greater ADFI than pigs fed DBM. There were no differences among treatments for DM or N digestibilities. For d 14 to 28, there were no differences in ADG or ADFI among treatments. However, pigs fed WPC and DBM had numerically greater ADG than pigs fed SDPP (.99 vs .95 lb/d) corresponding closely with the 5% improvement in F/G. Overall (d 0 to 28), there were no differences in ADG among treatments. However, pigs fed SDPP consumed more feed and had poorer FIG compared to pigs fed WPC and DBM. Considering overall pig performance, WPC, DBM, and SDPP are acceptable substitutes for DSM in diets for early-weaned pigs.
Keywords: Swine; Whey protein concentrate; Dried buttermilk; Porcine plasma; Skim milk; Nursery